PENGEMBANGAN SUPLEMEN BAHAN AJAR BERBENTUK BOOKLET MATERI PESAWAT SEDERHANA KELAS VIII SMP KUBURAYA - Novianti, Maria Dian; Sitompul, Stepanus Sahala; Mahmuda, Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research and development aims to develop supplementary teaching materials in the form of booklets that are suitable for use by junior high school students in grade VIII. the method used embraces research and development by borg and gall which includes 7 stages out of 10 stages. conducted the feasibility test, content validity test and student response test. the results obtained in the feasibility test include aspects of the display 84.74%, aspects of the presentation of material 78.46% and aspects of the benefits 81.46%. the results of the validity test aspects of the feasibility of the contents, the feasibility of presentation, the assessment of language and the feasibility of graphic conclusions booklet supplement teaching materials are appropriate to use. and got 81.76% of student responses.